A review of the Cnemidophorus lemniscatus group in Central America (Squamata: Teiidae), with comments on other species in the group - Mccranie, James R.; Hedges, S. Blair (Zootaxa, 2013)
We provide the results of a morphological and molecular study on the Honduran Bay Island and mainland populations of the Cnemidophorus lemniscatus complex for which we resurrect C. ruatanus comb. nov. as a full species. Morphological comparison of the Honduran populations to Cnemidophorus populations from Panama led to the conclusion that the Panamanian population represents an undescribed species named herein. In light of these new results, and considering past morphological studies of several South American populations of the C. lemniscatus group, we suggest that three other nominal forms of the group are best treated as valid species: C. espeuti (described as a full species, but subsequently treated as a synonym of C. lemniscatus or a subspecies of C. lemniscatus until this publication), C. gaigei comb. nov., and C. splendidus comb. nov.